Interpreting Cardiac Electrograms From Skin to Endocardium - Michael, Kevin A. (IntechOpen, 2017)
This is a reference book aimed at cardiologists, electrophysiologists and fellows in training. It presents an expansive review of cardiac electrogram interpretation in a collation of manuscripts that represent clinical studies, relevant anecdotal cases and basic science chapters evaluating cardiac signal processing pertaining to persistent atrial fibrillation. A diagnostic approach to arrhythmias using a standard ECG, the signal average ECG and fetal ECG is highlighted. Intracardiac ICD electrograms are also explored in terms of trouble shooting and device programming.